A Microstructure, Piezoelectric and Dielectric Properties of the PZT Ceramics Obtained by the Sol-Gel Method - DUKAT, Monika; ZARYCKA, Aldona (Archives of Acoustics, 2008)
A technological process to obtain ceramic materials by the sol-gel method replaces graduallyconventional methods, based on a simple oxide synthesis as a result of high temperaturesintering. The materials obtained by the sol-gel method are characterized by high density andbetter chemical purity. A powder with the Pb(Zr0:52Ti0:48)O3 chemical composition was obtainedas a result of a synthesis by the sol-gel method and it was formed and sintered by a hotpressing method (HP). The specimens obtained were subjected to examinations of the dielectricproperties, the tangent of dielectric loss angle, the piezoelectric properties and theirmicro-photographs were taken (SEM).A course of the technological process by the sol-gel method was described, the dielectricand piezoelectric parameters were determined and a microstructure and a domain structurewere examined in the work.